Poetic exquisite corpse: politicizing literary genders through didactic strategies. - Robles Murillo, Keylor (2020)
The present essay puts forward the process and development of the didactic strategy entitled “Poetic exquisite corpse,” which was carried out as part of the formative and summative evaluations of the course ED0012 Didáctica General at Universidad de Costa Rica, Sede Occidente. The purpose of this text is to present a creativity-based strategy where the postulates of surrealism are articulated in order to consolidate a collective work that allows for group reflection. In like manner, its implications in two different directions are discussed: a) the pedagogical level from a critical perspective and b) in the specific area of Spanish teaching. Finally, conclusions are shared.